DIDACTIC TASKS IN THE LANDSCAPE DRAWING PROCESS AND THEIR EFFECTIVENESS - Amonova Durdona Aliek qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article explores didactic tasks used in the landscape drawing process and evaluates their effectiveness in enhancing students’ artistic skills, visual thinking, and creativity. The study emphasizes the role of structured exercises, observation tasks, interactive activities, and individual and group assignments in developing compositional understanding, color perception, and spatial awareness. The article also highlights strategies for assessing the effectiveness of these tasks, providing constructive feedback, and adapting exercises to maximize student engagement and learning outcomes.